Optimasi Kualitas Citra Radiografi Abdomen Berdasarkan Body Mass Index dan Tegangan Tabung pada Computed Radiography - Siti Rosidah; Ari Soewondo; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2020)
Background: Computed Radiography is a modality of radiographic processing that has wide-exposure latitude. So that in radiographic examination with CR modality is less concerned with the accuracy of the exposure factor especially in the use of tube voltage that can affect the image quality. Image quality determines the accuracy of diagnosis of an illness. Abdominal examination is often done in the radiological installation of Hospital, with different patient conditions especially in Body Mass Index the use of tube voltages tends to vary so as to affect the quality of radiograph and received dose PatientsMethods: This type of research is analytical observational research with cross sectional research draft. Samples in research amounted to 108 distributed in each group of Body mass Index (underweight, normal, overweight) respectively 36 samples. Each body mass index group sample is taken from the use of tube voltages that are often used in RS 75 kV, 80kV, 85 kV and 90 kV respectively as much as 9. Assessments include the value of the exposure index, Noise and anatomical information. Statistical data analysis with Spearman test and univariat.Result: There is a significant connection between the use of cylinder voltage with an index exposure, noise and anatomical imageryConclusion : Optimised tube voltage for Body Mass index Under 75 kV, normal BMI 80 kV and BMI over 85 kV